A Blockchain and modified Best-worst algorithm enhanced Blackboard model for stranger collaboration based social product design. (January 2023) - Yang, Maolin; Jiang, Pingyu; Liu, Jiajun
Highlights: A management and control model for Social product design (SPD) is established. The model integrates Blackboard, Blockchain, and Best-worst algorithm. The model reduces the time cost for participating complicated SPD projects. The model improves the collaboration efficiency and controllability of SPD projects. The model provides the basis for intellectual property protection in SPD projects. Abstract: Social product design (SPD) is a new kind of product design pattern emerged under the background of sharing economic trends and fast developing online communication technologies. Due to the participation of large numbers of socialized designers (SDs), SPD pattern has the capability of utilizing socialized design resources to increase the design power of design companies with relatively lower costs. However, the SDs have the characteristics of self-driven, self-organized, unaffiliated, distributed and discontinuous participation, and stranger collaboration. These characteristics lead to the problems of low collaboration efficiency, low controllability, and low mutual trust during SPD process. Consequently these problems could limit the industrial application of SPD in relatively complicated and intellectual property issues involved design projects. Addressing these problems, a Blockchain and modified Best-worst algorithm enhanced Blackboard model is established. The Blackboard model with customized components can improve the collaboration efficiency and orderliness among SDs. The Blockchain can realize reliable recording of the discontinuous participation of SDs in SPD process. On this basis, a modified Best-Worst algorithm is established to support the estimation of the contribution degrees of SDs during SPD process. Combined together, the model can improve the operability of SPD application. A 3D printer concept design project was used as case study, and the result shows that the model can improve the operability of SPD pattern in relatively complicated and intellectual property issues involved design projects compared with ordinary crowdsourcing or opensourcing design models, but its higher operating cost may limit its application only for high valued design projects.